Utilization of Fiber Empty Bunches of Palm Oil as a growing medium of Pleurotus ostreatus - Hidayati Hidayati; Mohammad Rusdi Hidayat (Balai Riset dan Standardisasi Industri Pontianak, 2015)
The Utilization of fiber empty bunches of palm oil as a medium for the growth of Pleurotus ostreatus is an effort to reduce waste in the palm oil industry. This research aims to determine the best formulation of fiber empty bunches from palm oil and sawdust as a growth medium for P. ostreatus. The results showed that the fiber combined with sawdust can be used as a medium for the growth of P. ostreatus in Pontianak. The Growth of mycelium, fruiting bodies, hoods diameter and number of fruiting bodies produced were different in each treatment group. The use of a mixture of 50% fiber without pretreatment and 50% sawdust (B2D0) gave the best results indicated from the weight of P. ostreatus was 149.39 g/baglog and biological efficiency was 49.8%.